Strategically Aligned Family Research Supporting Soldier and Family Quality of Life Research for Policy Decisionmaking - Sims, Carra S. (RAND Corporation, 2013)
The Army spends a great deal on soldier and family support or quality of life (QOL) programs intended to ease the stress of military life and thus enhance well-being, improve readiness, and sustain recruiting and retention. The Army wants to develop a research agenda that defines the QOL needs of soldiers and families, helps gauge the success of programs, improves coordination of research efforts, and determines how best to allocate resources.